Magnetic Separation of Calcite Using Selective Magnetite Coating. (1999) - Prakash, S.; Das, B.; Venugopal, R.
Abstract : Magnetic separation of naturally occurring calcite (98.2% CaCO3 ) using selective coating of synthetic colloidal magnetite with sodium oleate has been investigated as a function of pH, concentration of colloidal magnetite, magnetic intensity and particle size. Colloidal magnetite treated with sodium oleate (oleate magnetite) is found to be a better coating agent than the natural magnetite. The mechanism of oleate magnetite coating has been investigated through adsorption and electrokinetics measurements. FTIR studies indicate that there is a possible chemical interaction between calcite and magnetite surfaces on which sodium oleate is adsorbed. Magnetic susceptibility measurement shows a finite susceptibility of calcite by the addition of colloidal magnetite. In the investigation with calcite, calcite recoveries of > 94% have been achieved at a colloidal magnetite concentration of 0.25 ml/g and 7.1 kG of magnetic intensity. In case of synthetic mixture of calcite and quartz > 90% calcite recovery at a grade of 80.9% CaCO3 has been achieved at the optimum pH of 11.